2001
DOI: 10.1063/1.1348275
|View full text |Cite
|
Sign up to set email alerts
|

The Jahn–Teller and related effects in the cyclopentadienyl radical. I. The ab initio calculation of spectroscopically observable parameters

Abstract: Ab initio calculations are performed for the X 2 E 1 and A 2 A 2 states of the cyclopentadienyl radical. An important goal of these calculations is to guide the analysis of the experimentally observed A 2 A 2-X 2 E 1 electronic spectrum. Vibrational frequencies for both theX andà state are reported. Large changes in frequency between the states for out-of-plane vibrations are found, leading to the expectation that overtones of these modes will appear strongly in the spectrum. Additionally, spectroscopically ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
133
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(147 citation statements)
references
References 43 publications
(42 reference statements)
14
133
0
Order By: Relevance
“…The best fit of the simulated NIPE spectrum to the experimental spectrum indicates that the ground state of HCPN 3 • is a 5π-electron 2 A″ π radical state, with a 6π-electron, 2 A′, σ radical state being at most 1.0 kcal/mol higher in energy.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The best fit of the simulated NIPE spectrum to the experimental spectrum indicates that the ground state of HCPN 3 • is a 5π-electron 2 A″ π radical state, with a 6π-electron, 2 A′, σ radical state being at most 1.0 kcal/mol higher in energy.…”
mentioning
confidence: 92%
“…19 The IE of (CH) 2 20 Comparisons of the (CH) 2 N 3 anion and radical with the previously studied (CH) 4 N 21 and (CH) 3 N 2 22,23 species found that substitution of each CH group in C 5 H 5 −/• by an isoelectronic N atom has a significant effect on the chemistry and thermodynamic properties, such as the C−H bond dissociation energies and gas-phase acidities, of these three nitrogen-containing analogues of C 5 24 This anion can be viewed as the n = 1 member of the series, (CH) 2-n P n N 3 − (n = 0−2). Nucleus-independent chemical shift (NICS) and quantum theory of atoms in molecules (QTAIM) calculations showed that HCPN 3 − is aromatic, with its aromaticity being intermediate between that of the n = 0 [(CH) 2 N 3 − ] and the n = 2 (P 2 N 3 − ) members of this series. In this paper we report the detailed results of NIPE spectroscopy and electronic structure calculations on HCPN 3 − and the neutral radical formed from it.…”
Section: Introductionmentioning
confidence: 99%
“…This molecule falls in the class of nitrogen containing five member ring compounds known as azolyls and can be viewed as a derivative of the well studied Jahn-Teller radical (CH) 5 , cyclopentadienyl, [16][17][18] which has a degenerate 2 E ′′ 1 ground electronic state derived from π orbitals. In triazolyl the minimum energy conical intersection (MEX) and minimum on the ground state potential energy surface, both of which have C 2v symmetry, are relatively well separated.…”
Section: Introductionmentioning
confidence: 99%
“…The key to understanding the spectra is a good estimate of the D's and ω's obtained using high level ab initio calculations. 18 Indeed, prior to these calculations the parameter space had proven far too great for a successful analysis of the spectra. …”
Section: Linear Jahn-teller Interactions: the Cyclopentadienyl Radicalmentioning
confidence: 99%